2018
DOI: 10.1108/jaee-05-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity on boards and forward-looking information disclosure: evidence from Jordan

Abstract: Purpose The purpose of this paper is to provide empirical evidence of the relationship between female representation on the board and forward-looking information disclosures (FLIDs). Design/methodology/approach The study uses the content analysis to analyze the narrative evidence from the annual financial reports of non-financial Jordanian companies listed on the Amman Stock Exchange. The final sample consists of 1,206 firm-year observations during the period 2008-2013. Findings The study provides evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 99 publications
(178 reference statements)
6
65
2
Order By: Relevance
“…H6 is accepted partially. The result is consistent with agency theory and with previous studies (Ammer and Ahmad-Zaluki 2017;Gull et al 2018;Aribi et al 2018;Bravo and Alcaide-Ruiz 2019). This could be because females have different capabilities than males due to the different socialisation processes for men and women (Srinidhi et al 2011).…”
Section: Ac Female Memberssupporting
confidence: 92%
See 1 more Smart Citation
“…H6 is accepted partially. The result is consistent with agency theory and with previous studies (Ammer and Ahmad-Zaluki 2017;Gull et al 2018;Aribi et al 2018;Bravo and Alcaide-Ruiz 2019). This could be because females have different capabilities than males due to the different socialisation processes for men and women (Srinidhi et al 2011).…”
Section: Ac Female Memberssupporting
confidence: 92%
“…Moreover, many previous studies find that companies with female directors are more likely to increase FRQ (proxied by different measures, such as less earnings management and higher audit quality) (Zalata et al 2018;Gull et al 2018;Bala et al 2020;Chee and Tham 2020;Saona et al 2020;Sultana et al 2020). In addition, Allini et al (2016), Al-Yahyaee et al (2017), and Aribi et al (2018) find that the presence of women on a board makes a significant difference to the quantity of risk disclosure, which improves the effectiveness of the board and enhance accountability and transparency.…”
Section: Ac Female Membership and Fldmentioning
confidence: 99%
“…Concerning the control variables (profile of the hotel manager), there are no significant differences in CSR communication decisions based on the gender or level of autonomy. The absence of a positive link between the manager's gender and CRS reporting contrasts with results from studies conducted outside the hotel industry in Malaysia (Darus et al, 2016), Kazakhstan (Orazalin, 2019), and Jordan (Aribi et al, 2018), which showed that a female presence on the board of directors positively influenced CSR disclosure. Since the aforementioned studies took place in Muslim-majority countries, it could be argued that cultural differences might influence this particular issue.…”
Section: Ta B L E 1 Profile Of the Sample (Hotels)contrasting
confidence: 63%
“…Academic researchers have also started looking into the impact of executive gender and its effect on voluntary information disclosure and found that female executives and voluntary disclosure of forward-looking information have a significant and positive association [76]. Based on this, in our next hypothesis, it is assumed that the effects of female participation in the executive team are also transferable to voluntary integrated reporting as follows:…”
Section: H1mentioning
confidence: 93%